Toxicity of poison from spider Nephila sp. to Aëdes aegypti L. larvae - YAYAN SANJAYA; TINA SAFARIA (Biodiversitas Journal of Biological Diversity, 2006)
A research about the toxicity of poison from spider Nephila sp. unto larvae of Aëdes aegypti L. had been done. The objectives of this research were to get the information about the toxicity of poison from spider Nephila sp. into larvae A. aegypti. The experiment method of this research was using Randomized Complete Block Design. This experiment used all of four instars of A. aegypti larvae. The experiment of each instar had been done with six treatments of the lethal concentration from spiders poison. Those six treatments were 1%, 10%, 25%, 50%, 75% and 100%. Each treatment had four replications. The result of this research showed that poison from spider Nephila sp. is toxic unto the larvae of A. aegypti. The average of lethal concentration for the first instar is 13.11%, for the second instar is 28.16%, for the third instar is 41.46% and for the fourth instar is 63.09%. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: toxicity, lethal concentration (LC50), spider Nephila sp. and larvae of Aëdes aegypti L.